Comparison of the histologic changes in conchae induced by radiofrequency thermal ablation and submucosal diathermy - Kaplama, Mehmet Erkan; Kaygusuz, Irfan; Akpolat, Nusret; Karlidag, Turgut; Keles, Erol; Alpay, Hayrettin Cengiz; Orhan, Israfil (Springer, 2013)
Objective of study was to determine the histological change induced in the conchae by submucosal diathermy and radiofrequency thermal ablation, two techniques used in the treatment of lower conchal hypertrophy, and to compare the two methods to each other. The study was performed on 15 rabbits. Radiofrequency was applied to the study animals in Group I (n = 5) and submucosal diathermy to Group II (n = 5), while Group III (n = 5) was the untreated control. The animals were decapitated 21 days after treatment and their conchae nasales ventrales excised on both sides. Histology slides were prepared and evaluated by light microscopy for ciliary loss, increase in submucosal vascularity, loss of goblet cells, inflammatory cellular infiltration, fibrosis and epithelial damage. The differences between Groups I and III were not significant regarding ciliary loss, increase in submucosal vascularity, loss of goblet cells and epithelial damage (p > 0.05), while the inflammatory cellular infiltration and fibrosis were significantly different between these groups (p < 0.05). As for the differences between Groups II and III, they were significant for each of the compared parameters (p < 0.05), while among Groups I and II they were significant for ciliary loss (p < 0.05), increase in submucosal vascularity, loss of goblet cells, inflammatory cellular infiltration and epithelial damage but not fibrosis (p > 0.05). Based on these findings, we can state that the use of radiofrequency thermal ablation causes less change in the normal conchal histology than submucosal diathermy application.
Keywords: Radiofrequency; Nasal conchae; Submucosal diathermy; Nasal obstruction